DISEASES OF THE ORAL CAVITY IN EMPLOYEES OF THE TEXTILE INDUSTRY WITH A WORK EXPERIENCE OF UP TO 9 YEARS IN 2 YEARS (Proceedings of International Conference on Scientific Research in Natural and Social Sciences, 2024)
The article uses various organic and inorganic paint solutions in painting - finishing enterprises in all branches of the manufacturing industry, in particular, the textile industry. These chemical dyes and solutions are a factor that calls autoallergenic reactions by denaturing proteins on the mucous membrane of the skin, respiratory tract. Clinical-experimental tests conducted by several scientists among workers of a manufacturing enterprise, in which organic and inorganic compounds were applied, comprehensively substantiated the negative effects of chemical dyes, reagents, catalysts and others on the tissues of the oral cavity and in the whole organism.